Genetic testing for Spinocerebellar Ataxias (SCA) in Parkinsonism (Bangladesh Journal of Neuroscience, 2013)
Objective: The study was conducted to find out Spinocerebellar Ataxias (SCA) by genetic analysis from those presenting with parkinsonism in the Neurology department of Mymensingh Medical College.Materials and methods: A sample of about 5ml blood was collected by venipuncture in EDTA tube with informed consent from the patients following institutional ethics committee approval by genetic study from 7 healthy people and 9 patients. The neurological disorder along with a complete physical and/or psychological, as well as family history and demographic data was recorded with a prescribed questionnaire by the neurologists of Mymensingh Medical College. Extraction of genomic DNA from the venous blood using FlexiGene DNA kit (Qiagen, Japan) was performed in Department of Medicine, Bangladesh Agricultural University, Mymensingh 2202, Bangladesh. The extracted DNA was stored and accumulated and then these DNA were sent to Division of Clinical Genetics, Department of Medical Genetics, Osaka University Medical School, Suita, Osaka 565 0871, Japan for PCR and further analysis. PCR amplification of the CAG repeat was performed for the SCA1, SCA2, SCA3, SCA6 loci using primers SCA1N-F1 and SCA1N-R1, SCA2-F1 and SCA2-R1, MJDF1 and MJDR1, SCA6-F1 and SCA6-R1, respectively.Results: SCA1 PCR of both healthy individual and suspected PD patients DNA is about 250 bp (no. of CAG repeats=36). SCA2 PCR products reveal the DNA products of about 150 bp (no. of CAG repeats=23) except one patient that we suspected and it was sequenced and revealed 175bp (no. of CAG repeats=30). SCA3 PCR product size of both healthy individual and patient DNA is within about 250 (no. of CAG=11) to 300 bp (no. of CAG repeats=28) except one patient which is about 320bp and its CAG repeats is about 34. SCA6 PCR product size of both healthy individual and patient DNA is about 150bp (no. of CAG=16).Conclusion: This is the first time from Bangladesh regarding the range of CAG repeats in patients as well as healthy individual.